Performance Analisys by Using Value For Money Approach at Food and Drug Agent in Padang at 2015 - 2017 (JURNAL ECONOMICA : Research of Economic And Economic Education, 2019)
Goverment performance achievement in servising public can be reach by adding budget. The purpose of this research are to see strategic planning, activity achievement performance, and efficiency of the activity done by food and drug agent in Padang for 2015 untill 2017. Food and drug agent in Padang is the branch of food and drug agent of Indonesia in Jakarta.The data used in this research are secondary datas. They are performance accountability report of goverment for year 2015, 2016 and 2017, strategic planning of food and drug agent of Indonesian Republic, strategic planning of food and drug agent in Padang, any rules related, any journals related. The focus of this research are strategic planning performance target, activity performance, and activity efficiency.The result of this research are, strategic planning is the guideline to do activity and function for each part of food and drug agent in Padang for five years. Achievement of activity performance for 2015 is 84,05 %, 2016 is 90,24% and 2017 is 91,17%. Activity efficiency of food and drug agent in Padang for 2015 until 2017 are already efficient.